The safety of government debt - Kartik Anand; Prasanna Gai (Bank of Canada, 2013)
We examine the safety of government bonds in the presence of Knightian uncertainty amongst financial market participants. In our model, the information insensitivity of government bonds is driven by strategic complementarities across counterparties and the structure of trading relationships. We identify the frontier between safe and unsafe assets and show how the growth rate of the economy and its fiscal capacity interact with the degree of ambiguity amongst investors to determine the safe-asset equilibrium. We use our framework to illustrate a fiscal variation on the Triffin dilemma, in which the role of a country as sole provider of international liquidity is questioned as its size in the world economy - and hence its fiscal capacity - diminishes.
Keywords: E44; D81; F02; F41; G15; 330; Economic models; Financial stability; International financial markets